An Assistance in the Use of Goat Manure Waste as Liquid Organic Fertilizer in Nagari Palaluar to Support Environmentally Friendly Agriculture - Maiyontoni Maiyontoni; Santi Diana Putri; Resti Fevria; Andi Alatas; Hermansah Hermansah; Agustian Agustian; Nurmiati Nurmiati (Pelita Eksakta, 2026)
Small-scale goat farmers in Nagari Palaluar, Koto VII District, Sijunjung Regency have a dual challenge in the form of low profitability of goat farming and degradation of agricultural land due to excessive use of inorganic fertilizers and conversion of former mining land. This community service initiative aims to increase farmers' income by converting goat manure waste by processing goat manure waste into Liquid Organic Fertilizer, while supporting sustainable agricultural practices. Using a participatory rural appraisal (PRA) approach, the program combines theoretical education, LOF (Liquid Organic Fertilizer) making practice training, technical mentoring, and laboratory-based evaluation. The results showed a very significant increase in knowledge (p < 0.001) with an average gain score of 39.00 (from 48.33 to 87.33). Laboratory analysis confirmed the quality of POC with macronutrient concentrations of Nitrogen (235.5 ppm), Phosphorus (299.7 ppm), and Potassium (714.7 ppm) at Level 1 (Very High), as well as an optimal pH of 6.8. The participants managed to produce 160 liters of LOF per month, creating a new source of income through local sales while reducing dependence on chemical fertilizers. This integrated approach not only increases the income of goat farmers but also promotes a circular economy, reduces environmental impact, and contributes to SDGs 12 and 15